"We Are in the Room to Serve Our Clients": We and Professional Identity Socialization in E-Mail Supervision of Counselors-in-Training. (January 2016) - Gordon, Cynthia; Luke, Melissa
This study uses computer-mediated discourse analysis to investigate use of the first-person plural pronoun "we" in e-mail supervision of 23 graduate-level counselors-in-training who are completing internships. Extending prior research on pronouns and relationship and identity construction, expert–novice discourse, professional identity socialization, and cybersupervision, our analysis highlights two prominent uses of "we" that differ by professional role: Interns primarily use exclusive we to refer to themselves and others (exclusive of e-mail supervisors) as they depict themselves interacting with others at their internship sites; supervisors overwhelmingly use professional we, meaning " you (the intern) and I, as part of the counseling profession" and thereby "invite" interns into the professional community of practice. These different uses reflect, reinforce, and bridge the gap in knowledge, experience, and professional identity between interns and supervisors. Findings contribute to understanding how professional identities and relationships are linguistically cultivated online. They also have potential practice implications for supervisors.